Role of Maternal Education in Promoting Antenatal Screening that Prevents Ophthalmia Neonatorum - Rashid, Muhammad Akbar; Hussain, Sajjad; Shahab, Areeba; Haq, Ehtisham ul; Fareed, Muhammad Sibtain (International Journal of Independent Research Studies, 2025)
Ophthalmia neonatorum (ON) is a serious avoidable cause of neonatal blindness, which is primarily caused by vertical transmission of Chlamydia trachomatis and Neisseria gonorrhoeae. This narrative review highlights the importance of maternal education on the promotion of antenatal screening and prevention of ON. In literature since 2020, maternal education has been shown to improve awareness, screening adherence and compliance with prophylaxis, and low education levels are associated with delayed care seeking and high-incidence of ON. Thematic synthesis determined that four concepts were of main significance: maternal education is a determinant of screening use, health literacy is a behavioral intermediary, socioeconomic and cultural moderators, and integration of educational programs in the antenatal care system. There is evidence to support the fact that the integration of maternal education into the process of antenatal care enhances the quality of neonatal eye health and reduces the rate of infection. Policy and practice implications include the need to implement educational interventions at the community level, need to incorporate the use of education in maternal health and need to include preventive counseling as part of the national guidelines. Increasing maternal education is therefore a long-term approach to lessening preventable neonatal blindness and improving equitable maternal-infant health worldwide.